Empowering Healthcare Transformation Through IoT and Big Data Integration in Remote Real-time Patient Monitoring - Sharma, Rashmi; Malik, Ashish; Pawar, Charu; Singh, Dev; Rufus, N. Herald Anantha (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The healthcare landscape is undergoing a significant transformation driven by the convergence of advanced technologies like the Internet of Things (IoT), big data, and artificial intelligence (AI). Remote real-time patient monitoring with IoT-based big data management and analytics emerges as a revolutionary paradigm, promising to redefine how we monitor and manage patient health. Remote Real-time Patient Monitoring (RRPM) has emerged as a transformative force in healthcare, particularly for chronic conditions like asthma seizures and heart failures. This paper explores the integration of RRPM systems with the Internet of Things (IoT) and Big Data technologies to revolutionize patient care. Using asthma and heart failure as case studies, we delve into the functionalities of RRPM systems, highlighting their ability to continuously collect and transmit vital signs, detect early warning signs of exacerbations, and facilitate proactive interventions. We then delve into the crucial role of IoT-based Big Data Management and Analytics (BDMA) in RRPM. This paper examines the challenges and opportunities presented by BDMA in healthcare, focusing on data acquisition, storage, analysis, and visualization. We analyze how advanced analytics like machine learning and artificial intelligence can enable predictive modeling, personalized care plans, and real-time decision support for healthcare professionals. Finally, we address the ethical and regulatory considerations surrounding patient data privacy and security within RRPM systems.